The methods and skills of history : a practical guide - Salevouris,Michael J. et al; Furay, Conal (UK. Wiley Blackwell, 2015)
"Widely acclaimed for its accessibility and engaging approach to the subject, the fourth edition of The Methods and Skills of History combines theory and instruction with hands-on practice, making it a comprehensive guide to historical research and writing. Combines theory with hands-on practice in its introduction to historical methods. Includes a series of field-tested exercises designed to make the research and writing of history more meaningful and accessible to readers. Features expanded coverage of writing history and up-to-date coverage of online research. Designed to strengthen students' critical thinking and communication skills"--
"Includes a series of field-tested exercises designed to make the research and writing of history more meaningful and accessible to readers"--
Includes bibliographical references and index.
Keywords: History -- Examinations, questions, etc; History -- Methodology; HISTORY / General